1996
DOI: 10.1093/brain/119.2.539
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anti–epileptic drugs on visual perception in patients with epilepsy

Abstract: We investigated the influence of the antiepileptic drugs carbamazepine (CBZ), phenytoin (PHT) and valproic acid (VPA) on different aspects of visual perception in patients with epilepsy by three different methods. (i) The colour arrangement test Farnsworth Munsell D100. (ii) A monitor system generating 24 different Gaussian dots and 24 different vertical sinusoidal gratings. Luminance increments and decrements for achromatic discrimination and four different colours for chromatic discrimination were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 27 publications
3
26
0
Order By: Relevance
“…However, reports of S‐cone deficits are not uncommon in various conditions (e.g. Parkinson's disease (39), multiple sclerosis (40), Huntington's chorea (41), epilepsy (42)) and also occur following centrally acting medication (43, 44). The preponderance of acquired S‐cone deficits may simply reflect that there are relatively few S‐cones, compared to the numbers of L‐ and M‐cones, so any alteration in visual processing is likely to present (initially) for S‐cone colours.…”
Section: Discussionmentioning
confidence: 99%
“…However, reports of S‐cone deficits are not uncommon in various conditions (e.g. Parkinson's disease (39), multiple sclerosis (40), Huntington's chorea (41), epilepsy (42)) and also occur following centrally acting medication (43, 44). The preponderance of acquired S‐cone deficits may simply reflect that there are relatively few S‐cones, compared to the numbers of L‐ and M‐cones, so any alteration in visual processing is likely to present (initially) for S‐cone colours.…”
Section: Discussionmentioning
confidence: 99%
“…Paulus et al [10], after testing visual function with three different physicophysical methods (F-100, sinusoidal colour and black-white gratings and blue test light) in patients exposed to PHT, CBZ and VPA, concluded that the F-100 was the most sensitive test for colour discrimination deficit. However, they failed to find a clear-cut colour preponderance, and the greatest score was observed in the PHT group followed by the VPA and CBZ groups, pointing out that qualitative differences for the blue test light (increased for PHT) and sinusoidal gratings (increased threshold for VPA) correlated better with retinal cell function than with cell cortical neurotransmission.…”
Section: Discussionmentioning
confidence: 99%
“…The possible impairment of contrast sensitivity secondary to carbamazepine therapy is still a matter of controversy. [119] Some researchers have found the presence of such an association, [120][121][122] while others found no association whatsoever. [123] Steinhoff et al [123] did not find any disturbance in colour perception when they delivered a single oral dose of carbamazepine to healthy individuals.…”
Section: Carbamazepinementioning
confidence: 99%